The aim of the study was to analyze the interaction between clone and environment for starch yield in six month-old plants of cassava clones based on additive main effects and multiplicative interaction (AMMI) model. The experiments were conducted on mineral soil in four different locations: Lumajang (inceptisol), Kediri (entisol), Pati (alfisol), and Tulangbawang (ultisol). The experiments were carried out during 2004-2005, using a split plot design withthree replications. The main plots were t - . SHOLIHIN (Bogor Agricultural University, Indonesia, 2011)
The aim of the study was to analyze the interaction between clone and environment for starch yield in six month-old plants of cassava clones based on additive main effects and multiplicative interaction (AMMI) model. The experiments were conducted on mineral soil in four different locations: Lumajang (inceptisol), Kediri (entisol), Pati (alfisol), and Tulangbawang (ultisol). The experiments were carried out during 2004-2005, using a split plot design withthree replications. The main plots were the simple and the improved technology. The clones used were fifteen clones. Parameter recorded was starch yield (kg/ha) of the 6 month old plants. The data were analyzed using the AMMI model. Based on the AMMI analysis, environmental factors being important in determining the stability of the starch yield were soil density for subsoil, pH of topsoil, and the maximum air humidity four months after planting. The clones of CMM97001-87, CMM97002-183, CMM97011-191, CMM97006-44, and Adhira 4 were identified as stable clones in starch yield within 6 month-old plants. CMM97007-235 was adapted to maximum relative humidity 4 months after planting and to lower pH of topsoil, whereas, MLG 10311 was adapted to lower bulk density. The mean starch yield of MLG 10311 was the highest six months after planting.